Peningkatan Pengetahua Kematangan Karir Siswa Smk Yosonegoro Magetan - Raihana, Permata Ashfi; Roesmalita, Mita; Mahira, Raisa Suri (Institut Teknologi dan Sains Mandala, 2024)
Abstract This research aims to improve the career maturity of students of SMK Yosonegoro in Magetan Regency, East Java. Career maturity is the readiness of individuals to face the tasks of career development according to their stage of development. However, some students of SMK Yosonegoro face challenges related to career maturity. To overcome this problem, the researchers conducted community service activities that included several stages, namely: interviewing BK and 2 students to obtain initial data on the problems faced by students; giving a career maturity scale consisting of 33 items to 16 grade 12 students as a sample to measure their level of career maturity before and after participating in psychoeducation; providing psychoeducation on career maturity that contains material on career maturity strategies and raising awareness about careers in the future for students; and analysis of post-test data using Excel to find the average and standard deviation to determine the category range of low, medium, and high on the post-test results. From the results of the post-test data analysis, it was found that most students (12 people) had a moderate level of career maturity, only one person had a low level of career maturity, and three people had a high level of career maturity. This shows that the psychoeducation given has a positive impact on increasing students’ career maturity.Thus, it can be concluded that this community service activity successfully helped students of SMK Yosonegoro in improving their career maturity according to their stage of career development. Keywords: Career Maturity, Psychoeducation, Vocational High School Students